Republic of San Marino : Staff Report for the 2006 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The 2006 Article IV Consultation on San Marino explains financial sector development and stability. A wide-ranging reform of the regulatory framework and supervision is under way to modernize the financial sector and make it conform to international standards. Executive Directors encouraged to continue with reforms to enhance institutional flexibility and help ease the economy's transition to increased reliance on high value-adding service sectors. They looked forward to further progress in adjusting San Marino's legislation to the highest international anti-money laundering standards.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet